2007
DOI: 10.1016/j.vaccine.2006.10.043
|View full text |Cite
|
Sign up to set email alerts
|

FLK-1-based minigene vaccines induce T cell-mediated suppression of angiogenesis and tumor protective immunity in syngeneic BALB/c mice

Abstract: Angiogenesis is a rate-limiting step in the development of tumors. Here, we demonstrate that oral minigene DNA vaccines against murine vascular endothelial growth factor receptor-2 (FLK-1), a self-antigen overexpressed on proliferating endothelial cells in the tumor vasculature, induced protection against tumors of different origin in syngeneic BALB/c mice. This protection is mediated by CD8 T cells, which specifically kill FLK-1 + endothelial cells, resulting in marked suppression of tumor angiogenesis. More … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Expression of VEGFR2 on endothelial cells and binding of VEGF-A leads to the rapid differentiation, proliferation and migration of these cells into tube-like structures. Because of this, VEGFR2 plays an important role in tumor growth, invasion and metastasis, 62,63 making it an attractive therapeutic target 64,65 for Listeria based delivery.…”
Section: Activation Of Adaptive and Innate Immunementioning
confidence: 99%
“…Expression of VEGFR2 on endothelial cells and binding of VEGF-A leads to the rapid differentiation, proliferation and migration of these cells into tube-like structures. Because of this, VEGFR2 plays an important role in tumor growth, invasion and metastasis, 62,63 making it an attractive therapeutic target 64,65 for Listeria based delivery.…”
Section: Activation Of Adaptive and Innate Immunementioning
confidence: 99%
“…Specific CTL responses against the vasculature of multiple tumor types have also been generated with DNA vaccines coding for both whole and partial forms of target proteins [140,141]. Treatment with a VEGFR2 cDNA vaccine carried by attenuated Salmonella typhimurium led to increased survival as well as immunity from tumor rechallenge in mouse models of colon cancer, Lewis lung carcinoma and melanoma through CTL-mediated lysis of ECs.…”
Section: Dna Vaccinesmentioning
confidence: 99%
“…In-depth in vitro immunogenicity studies indicated that CD8+ T cells were responsible for the observed anti-tumor effect and that this CD8 + T cell immune response was specifically induced against FLK 400 , which is a H-2D b restricted FLK-1 epitope. In order to provide more proof of the efficacy of this vaccination approach this research group published on a similar VEGFR2 DNA mini-gene vaccine in another mouse strain with a different genetic background (BALB/c) [74]. Five VEGFR2 peptides were included in the studies and all mini-gene vaccines induced tumor protection, showing the general applicability of this approach across different genetic backgrounds with varying MHC restrictions.…”
Section: Vegfr2mentioning
confidence: 99%